Development of Novel Forms in Contemporary Mongolian Literature (21st century) - Petrova, Maria (Acta Mongolica, 2018)
The article analyses contemporary Mongolian literature development, distinguishing novel forms. The main rationale of the article is to classify the basic torrent of modern novels according to used literary strategy. Mongolian literature entered the 21st century being equipped with the European genre system, reviving national traditions and rich experience of realistic reality description. In the past 20th century the Mongolian literature genre system has made a very important transition from medieval literature to the Western European type. Poetry, that traditionally was prevailing over prose in the foreseeable historical period at the end of the 20th century has lost its quantitative superiority. The nature of any country or age literaryhistorical process largely depends on the development of a novel - one of the most demanded genres for today. In order to determine the orientation and outline the main lines of literary process further development in general, highlight the iconic names in the field of contemporary mosaic art of Mongolian literature it makes sense to apply to novel genre. Mongolian literary scholars and critics pay attention to it as well. We turn to this universal genre from the perspective of the development of traditional and new narrative strategies. 21st century Mongolian novelists give us this extensive factual material. Using the method of historical and literary analysis of contemporary authors works, we can divide the novel genre development into three main directions: realistic, modernist and postmodernist.